Use of bio-optical profiling float data in validation of ocean colour satellite products in a remote ocean region - Wojtasiewicz, B.; Hardman-Mountford, N.; Antoine, David; Dufois, F.; Slawinski, D.; Trull, T. (Elsevier, 2018)
Utility of data from autonomous profiling floats for the validation of satellite ocean colour products from current satellite ocean colour sensors was assessed using radiometric and chlorophyll a fluorescence data from biogeochemical profiling floats (BGC-Argo) deployed in the subtropical gyre of the Indian Ocean. One of the floats was equipped with downward irradiance and upwelling radiance sensors, allowing the remote sensing reflectance, R rs , to be determined. Comparisons between satellite and in situ R rs indicated good agreement for the shorter wavelengths, but weak relationships for both satellites for the 555 nm channel, and showed that radiometers deployed on multipurpose, off-the-shelf BGC-Argo floats can provide validation-quality measurements. About 300 chlorophyll a concentration match-ups were achieved within 18 months, which increased the number of validation data points available for the Indian Ocean as a whole by a factor of ~4 from the previous historical record. Generally, the satellite data agreed with the float-derived chlorophyll concentration within the uncertainty of Â±35%, for the band-difference (OCI) and band-ratio (OC3) algorithms, but not for a semianalytical ocean colour model (GSM) that exhibited significantly higher chlorophyll values ( > 100% mean difference). Our results indicate that autonomous float-based measurements provide substantial potential for improving regional validation of satellite ocean colour products in remote areas.